High-frequency EPR and ENDOR spectroscopy of Mn²+ ions in CdSe/CdMnS nanoplatelets - Babunts, Roman A. (2023)
Semiconductor colloidal nanoplatelets based of CdSe have excellent optical properties. Their magneto-optical and spin-dependent properties can be greatly modified by implementing magnetic Mn2+ ions, using concepts well established for diluted magnetic semiconductors. A variety of magnetic resonance techniques based on high-frequency (94 GHz) electron paramagnetic resonance in continuous wave and pulsed mode were used to get detailed information on the spin structure and spin dynamics of Mn2+ ions in core/shell CdSe/(Cd,Mn)S nanoplatelets. We observed two sets of resonances assigned to the Mn2+ ions inside the shell and at the nanoplatelet surface. The surface Mn demonstrates a considerably longer spin dynamics than the inner Mn due to lower amount of surrounding Mn2+ ions. The interaction between surface Mn2+ ions and 1H nuclei belonging to oleic acid ligands is measured by means of electron nuclear double resonance. This allowed us to estimate the distances between the Mn2+ ions and 1H nuclei, which equal to 0.31 ± 0.04, 0.44 ± 0.09, and more than 0.53 nm. This study shows that the Mn2+ ions can serve as atomic-size probes for studying the ligand attachment to the nanoplatelet surface.